2016
DOI: 10.1177/0093650215609669
|View full text |Cite
|
Sign up to set email alerts
|

Are Graphic Cigarette Warning Labels an Effective Message Strategy? A Test of Psychological Reactance Theory and Source Appraisal

Abstract: The purpose of this study is to examine psychological reactance in response to graphic cigarette warning labels and to strengthen and expand on the current literature by using validated measures. Young adults (N = 435) were randomly assigned to a cigarette package featuring a graphic image or a package featuring no image. Utilizing both structural equation modeling and multivariate analyses, the results indicate that graphic warning labels are associated with freedom threat perceptions directly and reactance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 52 publications
4
69
2
1
Order By: Relevance
“…However, with the exception of willingness to smoke, each of the observed differences was in the expected direction. Contrary to previous research demonstrating that pictorial warnings elicit reactance among adults [21,36,37], we did not find that reactance among adolescents differed between study arms. As reactance derives from a perceived threat to one's freedom [38], adolescents could have experienced greater reactance due to a newfound need for independence and autonomy [39].…”
Section: Discussioncontrasting
confidence: 99%
“…However, with the exception of willingness to smoke, each of the observed differences was in the expected direction. Contrary to previous research demonstrating that pictorial warnings elicit reactance among adults [21,36,37], we did not find that reactance among adolescents differed between study arms. As reactance derives from a perceived threat to one's freedom [38], adolescents could have experienced greater reactance due to a newfound need for independence and autonomy [39].…”
Section: Discussioncontrasting
confidence: 99%
“…Pictorial cigarette pack warnings cause greater message reactance than text warnings, as several studies and a recent meta-analysis have demonstrated (Erceg-Hurn & Steed, 2011; Hall et al, 2016; LaVoie et al, 2015; Noar et al, 2016). However, given the large body of research indicating the effectiveness of pictorial warnings, it would be unwise to conclude that pictorial warnings are counterproductive because they produce reactance, as others have asserted (LaVoie et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…However, given the large body of research indicating the effectiveness of pictorial warnings, it would be unwise to conclude that pictorial warnings are counterproductive because they produce reactance, as others have asserted (LaVoie et al, 2015). Experimental and observational evidence supports the superiority of pictorial warnings over text warnings on numerous outcomes, including quit intentions (Noar et al, 2016), quit attempts (Brewer et al, 2016), knowledge about smoking risks (Brennan et al, 2011), and foregoing cigarettes (Yong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The present research also highlights the promise of pictorial warnings as an effective tobacco control strategy, as pictorial warnings were viewed as more motivating than text warnings. Given the large body of research indicating the effectiveness of pictorial warnings, it would be unwise to conclude that pictorial warnings are counterproductive simply because they produce reactance, as others have done (20). However, our research suggests that reactance may partially weaken the impact of pictorial warnings on perceived effectiveness and the ability of the warning to motivate quitting, although text-only warnings performed worse overall.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, reactance may weaken the intended impact of the message (e.g., quitting smoking) or lead to boomerang effects (e.g., increased smoking). Experimental studies have focused on whether pictorial warnings increase reactance, but have not explored whether reactance undermines their positive effects (1820). Thus, we explore the potential undermining effects of reactance through three additional hypotheses.…”
mentioning
confidence: 99%